(untitled) (REVISTA SAYWA, 2020)
The phytopathogenic bacterium Xanthomonas phaseoli pv. manihotis (Xpm) is the causal agent of cassava bacterial blight, a disease that has been reported in all regions where cassava is grown. Xpm has been considered a medium risk pathogen due to the high diversity indexes and the high migration rates of its populations. Traditionally, adult cassava plants grown in the greenhouse have been used to determine the pathogenic behavior of Xpm isolates. In this work in vitro grown cassava plants were used to determine the resistance or susceptibility to three Xpm isolates and the results were compared with the same test with adult cassava plants. The results show that, although the values of AUDPC are higher for in vitro plants, there is a correspondence regarding the determination of resistance or susceptibility compared with adult plants.